Pelindungan Hukum Indikasi Geografis Tanaman Kemenyan Bunga di Kabupaten Pakpak Bharat - Sitohang, Agung Torang; Gultom, Latifah Hanum; Fitria Sinaga, Rahma Dhani; Trisna, Wulan Ayu; Siahaan, Parlaungan Gabriel; Beru Perangin angin, Reh Bungana (University of Merdeka Malang, 2023)
Geographical Indications are an important component of Intellectual Property Rights which relate to regional naming and the origin of products. The wealth of products originating from Geographical Indications has great potential for society and the country if managed well. The aim of this research is to analyze the legal protection of frankincense plants for geographical indications in Pakpak Bharat Regency. The main problem in this research is how to legally protect the geographical indications of frankincense plants in Pak-Pak Bharat Regency. The research method used is qualitative descriptive research with data collection through observation, interviews and literature study. The results of this research indicate that to obtain legal protection as a Geographical Indication for Pakpak Bharat Regency, flower incense must first be registered with the Directorate General of Intellectual Property Rights by fulfilling the requirements stated in the Geographical Indication requirements book. The positive impact of this legal protection is that the Pakpak Bharat community can obtain a Geographical Indication certificate and have collective rights to Pakpak Bharat flower incense, which allows them to use the Geographical Indication name exclusively.